Conspirituality and meme culture: transgressive dynamics in right-wing esoteric social media discourse - Maurer, Moritz (Religion, 2025)
The article delves into the processes shaping religion on the Internet, aiming to comprehend how content is created and disseminated online. Focusing on contemporary esotericism, especially conspirituality and right-wing esotericism, the study investigates two key mechanisms: transgressive behavior and the remixing and reframing of media in virtual spaces, especially in the form of memes. The analysis explores how these social and technological factors blur the boundaries between sincere adherence and ironic engagement with specific esoteric traditions. By examining these multifaceted dynamics, we can deepen our understanding of how religious actors operate online and Social Media’s impact on the field. The chosen perspective is part of a trend to expand the field of modern esoteric research beyond the consideration of elite discourses.